SOLUSI ALTERNATIF KEMACETAN DENGAN MOBILE APPS NEBENGERS 2.0 MENGGUNAKAN PENDEKATAN TECHNOLOGY ACCEPTANCE MODEL (TAM) (Jurnal Pilar Nusa Mandiri, 2013)
Traffic congestion in urban areas is a major problem at this time, efforts to reduce traffic congestion with alternative solutions making mobile apps Nebengers 2.0 which contains the share of transport. Nebengers 2.0 is the purpose of the alternative solutions to facilitate the search tebengan or share a ride to the base location. Features include a review profiles to strengthen security and to encourage users to be more extensive socializing. This project requires the support of all parties in order to provide a broader solution. Contribution to this application is a testament to the community in terms of social helplessness and transportation. TAM (Technology Acceptance Model) Approach aims to analyze how individual beliefs user information influenced their decision to accept or reject the use of information systems within mobile apps nebenger 2.0.